Structural and behavioural independence: mapping the meaning of agency independence at the field level. (June 2014) - Jackson, Carolyn
For regulators, independence is associated with good governance, reform and best practice. It has become one of the most claimed characteristics of the regulatory state. But what does it really mean to be an independent agency? This article explores this question with stakeholders of five privacy (and information) commissions to map the understanding of those actually involved in the everyday processes of regulation. It is argued that the beliefs and expectations of stakeholders shape not only relationships but ultimately the legitimacy of regulatory practices. Six separate themes of understanding are identified. The themes represent areas of particular concern for each stakeholder group. Together they suggest a shared understanding of independence that encompasses both behavioural qualities as well as structural arrangements. A framework is proposed that provides a means for incorporating the different accounts of independence and recognizing the active role of agencies in determining independence. Points for practitioners: Agency independence relates to behavioural qualities as well as structural arrangements. Behavioural qualities of independence encompass championing public interest, engendering trust and demonstrating impartiality. Procedures and routines based on clear principles of procedural fairness and transparency are likely to enhance agency independence.